Design of fluorescence turn-on sensors with novel response mechanism based on CN isomerization. (November 2021) - Zhong, Kailiang; Liu, Hailing; Jin, Shu; Chen, Xingliang
Abstract: A series of new type naphthalimide-based fluorescent molecules linking aniline-like groups via a coupling chain with –CN– structure were developed as novel fluorescence chemosensors with high sensitivity and selectivity toward H + in solution and acidic atmosphere as well as Al 3+ in the presence of other cations. The fluorescence turn-on mechanism was studied and proved to be based on the CN isomerization. For these fluorescent molecules with donor-acceptor structure, their luminescent wavelength and photophysical properties can be dominated by adjusting the structure of aniline-like groups and the chain length connecting with naphthalimide. All of these fluorescent molecules emitted strong solid-state fluorescence due to their inherent twisted geometries, and exhibited excellent thermal stability, which is beneficial for their application at high temperature. Graphical abstract: Image 1 Highlights: Novel naphthalimide-based derivatives with D-A structure were synthesized. These compounds show fluorescence turn-on property with the response mechanism based on CN isomerization. These compounds exhibit potential value for developing novel colorimetric pH and ions sensors.